Sweet cherries from the end of the world: options and constraints for fruit production systems in South Patagonia, Argentina - Cittadini, Eduardo Daniel (Wageningen University, 2020)
Tesis para obtener el grado de Philosophical Doctor (PhD), de la Wageningen University, en 2007